Shared Decision Making With Young People at Ultra High Risk of Psychotic Disorder - Simmons, Magenta Bender; Brushe, Mary; Elmes, Aurora; Polari, Andrea; Nelson, Barnaby; Montague, Alice (Frontiers in Psychiatry, 2021)
Introduction While the majority of young people who meet the criteria for being considered at increased risk of psychosis do not go on to develop a psychotic disorder, young people are currently being identified and treated in early intervention services. Ethical concerns have been raised concerning the decision about whether or not to provide treatment, and if so, what type of treatment. This study sought to support young people themselves to make these decisions with support from their clinician through a shared decision-making approach, facilitated by an online decision aid. Methods This project used the International Patient Decision Aid Standards to guide the development and piloting of an online decision aid across two phases: 1) qualitative, semi-structured focus groups with young people who were past clients and clinicians from an early psychosis service; and 2) pilot testing of the decision aid with clinicians and young people who were current clients to finalise the development. Results Issues discussed by clinicians in the focus group were grouped into three main areas: 1) engagement phase; 2) assessment and priorities for treatment; and 3) initial and ongoing decision making. Clients focused on the context in which the decisions were made, including as they experienced initial feelings of resistance, and then acceptance of efforts made to describe and treat their mental health challenges. Clients highlighted the need for collaboration between themselves and their clinician, and their need to be equipped with the knowledge and tools to take care of themselves. These focus group data were used to refine the online decision aid. Pilot testing revealed that while it was overall useful and relevant, important limitations were noted by both clients and clinicians. Discussion The use of a decision aid to facilitate shared decision making in this area is feasible and has utility for both clients and clinicians. Use of such a tool can help to address the need to uphold the rights of young people as decision makers about their own care. Future efforts should embed decision aids within complex shared decision making interventions, and research to understand issues relating to implementation of these interventions.